The Effect of the Relay Writing Method on Students' Narrative Writing Skills: Pengaruh Metode Estafet Writing Terhadap Keterampilan Menulis Karangan Narasi Siswa - Dwilina, Titin; R, Luluk Iffatur (Indonesian Journal of Education Methods Development, 2022)
This writing skill is very necessary for students, because in writing activities students can develop intelligence, and writing also encourages habits as well as fostering the ability to find, collect, and organize information. The formulation of the research problem is whether there is an effect of the relay writing method on the narrative writing skills of grade III students of SDN Balonggarut? How much influence does the relay writing method have on the writing skills of grade III students of SDN Balonggarut? This type of research is quantitative using saturated sampling. The results of this study indicate that there is an effect of the relay writing method on the narrative essay writing skills of students of SDN Balonggarut proven by testing using SPSS 18 with a t count of 2.492 while the t tabel with t is 0.05 of 1.813 and the relay writing method has a major influence on skills. writing narrative essays for third grade students of SDN Balonggarut as proven by the calculation of eta squared with the results of 0.383> 0.14 can be said to have a big effect.